Attributes of an Effective Mentor in a Learning Community: Comparison of Mentor and Mentee Perspectives - E. Whitney Pollio; Laila Abbas; Waqas Haque; James Wagner; Carol S. North; David E. Pollio (International Medical Education, 2025)
Acknowledgement of the importance of students interacting with faculty in a social context has prompted the development of Learning Communities (LCs) in many medical schools. Understanding successful LC and fruitful mentor–mentee relationships is essential to recognize the perspective of multiple stakeholders, i.e., both mentors and mentees. This study used inductive qualitative analysis methods to compare the key attributes and competencies of mentors that are most important to mentors with those most important to mentees in LCs. Six mentor focus groups (N = 50) and four mentee focus groups (N = 22) were conducted. Thematic analysis revealed twelve distinct themes. Three were categorized as mentor/mentee similarities: (1a) individualized approach, (1b) history and physical skills, and (1c) group interaction. Three were categorized as mentor/mentee differences: (2a) teaching versus relationship competence, (2b) mentor as a relatable figure, and (2c) faculty development. Four themes were unique to mentees: (3a) cultural competence and role modeling, (3b) feedback to students, (3c) one-on-one sessions, and (3d) clinical pearls, and two themes were unique to mentors: (4a) communication and (4b) peer development. Formative evaluation is needed to recognize new styles of learning preferences and new forms of feedback. Awareness of the similarities and differences in the perspectives of mentors and mentees can inform modifications to LCs that can potentially improve the experience of both mentors and mentees.